Visual Language and Inclusive Media Education: The Role of Sign Language in News Communication for Deaf Audiences - Clara Dubois (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2009)
This study explores the integration of sign language in news presentations as a strategy to promote inclusive media education and enhance linguistic accessibility for deaf audiences. A purposive sampling technique was employed, and data were collected through structured questionnaires and supported by qualitative analysis to capture participants’ experiences and perceptions regarding sign language in televised news. Findings indicate that the use of sign language in news broadcasting significantly improves comprehension, engagement, and information retention among deaf viewers. From a linguistic perspective, sign language facilitates meaningful interpretation of complex messages, while from an artistic perspective, it contributes to the visual and performative dimensions of media communication. Educationally, exposure to sign-interpreted news supports media literacy development and encourages active participation in social and civic life. The study further reveals that consistent integration of sign language in media platforms fosters inclusive learning environments and strengthens the relationship between language, visual arts, and communication. However, challenges such as limited availability of trained interpreters and inconsistent implementation across media institutions remain significant barriers. This study recommends the incorporation of sign language-based media content into educational curricula for hearing-impaired learners, as well as policy support for standardized use of sign language in news broadcasting. Strengthening collaboration between educators, media practitioners, and policymakers is essential to advance inclusive communication and sustainable media practices.